The Relationship between Self-Motivation and Diet Compliance in Hypertension Patients at Mitra Medika Hospital in Medan - Rudi Purwana; Afina Muharani Syaftriani; Maya Ardilla Siregar; Riani Baiduri Siregar (Jurnal Kesehatan LLDikti Wilayah 1 (JUKES), 2023)
Hypertension is a condition when the blood pressure in the blood vessels increases. The majority of hypertensive patients have non-compliance with their meal plans. If people with hypertension do not follow a hypertension diet, the risk of morbidity, death and complications from other diseases will increase. The best way to follow a hypertension diet is to motivate yourself.This study aims to identify the relationship between self-motivation and dietary adherence in hypertensionMitra Medika Hospital Medan. PThis research is a quantitative research which is an analytic survey with a cross sectional approach. The population used in this study were all hypertensive patients who were in the poly room of Mitra Medika General Hospital Medan, totaling 308 people.The sample in this study amounted to 75 people. The sampling technique in this study was purposive sampling with the inclusion criteria in this study being hypertensive patients who were outpatient at Mitra Medika Hospital in Medan and willing to be respondents.Data analysis used in this study was univariate and bivariate analysis. Based on the results of the chi-square test, the p-value (0.000 < ? (0.05), this proves that there is a relationship betweenself motivated withdietary compliance in hypertensive patients at Mitra Medika Hospital Medan. This study concluded that there is a relationship betweenself motivated withdietary compliance in hypertensive patients at Mitra Medika General Hospital Medan. It is recommended for hypertensive patients to improve and increase dietary compliance in order to maintain the patient's blood pressure levels.